Deficit of circulating CD19+CD24hiCD38hi regulatory B cells in severe aplastic anaemia. (20th April 2020) - Zaimoku, Yoshitaka; Patel, Bhavisha A.; Kajigaya, Sachiko; Feng, Xingmin; Alemu, Lemlem; Quinones Raffo, Diego; Groarke, Emma M.; Young, Neal S.
Abstract: Immune aplastic anaemia (AA) is caused by cytotoxic T lymphocytes (CTLs) that destroy haematopoietic stem and progenitor cells. Enhanced type 1 T helper (Th1) responses and reduced regulatory T cells (Tregs) are involved in the immune pathophysiology. CD24 hi CD38 hi regulatory B cells (Bregs) suppress CTLs and Th1 responses, and induce Tregs via interleukin 10 (IL‐10). We investigated circulating B‐cell subpopulations, including CD24 hi CD38 hi Bregs, as well as total B cells, CD4 + T cells, CD8 + T cells and natural killer cells in 104 untreated patients with severe and very severe AA, aged ≥18 years. All patients were treated with standard immunosuppressive therapy (IST) plus eltrombopag. CD24 hi CD38 hi Bregs were markedly reduced in patients with AA compared to healthy individuals, especially in very severe AA, but residual Bregs remained functional, capable of producing IL‐10; total B‐cell counts and the other B‐cell subpopulations were similar to those of healthy individuals. CD24 hi CD38 hi Bregs did not correlate with responses to IST, and they recovered to levels present in healthy individuals after therapy. Mature naïve B‐cell counts were unexpectedly associated with IST response. Markedly reduced CD24 hi CD38 hi Bregs, especially in very severe AA, with recovery after IST suggest Breg deficits may contribute to the pathophysiology of immune AA.